Forum de las Cultura. Barcellona, maggio-settembre 2004 - Dall’Ara, Enrica (Ri-Vista. Research for landscape architecture, 2015)
The Barcelona Forum event is a part of the implementation of the Agenda 21 for Culture which expresses the necessity of research into sustainable relations between the international community and local cultures. With conferences, expositions, performances, Barcelona opens the debate on the themes “Cultural diversity, sustainable development and conditions for peace”, with a program that takes up all the summer season 2004. The setting is a reclaimed urban area that Barcelona adds as a new part of the city to its tourist offer and to the pleasures of collective spaces for its citizens.